Enhancing Consumer Interest through Salam Contract Implementation in Sharia-Based Poultry Agribusiness - Nur Farida; Moh. Holil Baitaputra (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2025)
This study examines the impact of implementing Salam contracts on consumer interest in the poultry agribusiness sector, specifically at Chicken Jaya Poultry Farm in Karang Duwak, Arosbaya. The Salam contract, a pre-paid sales agreement with future delivery, has emerged as a Sharia-compliant financing model that reduces risks and enhances transaction transparency in agricultural businesses. The research employs a qualitative approach, using triangulation to gather data through in-depth interviews, direct observations, and documentation. Findings indicate that the implementation of Salam contracts has significantly contributed to increased consumer loyalty, fostered greater transparency between producers and consumers, and stabilised product prices. Furthermore, the study highlights the potential of Salam contracts to improve consumer trust and satisfaction, offering a viable alternative to conventional financing methods in agribusiness. This research contributes to the growing body of literature on the practical applications of Salam contracts in small-scale agricultural enterprises, suggesting that such contracts could be an effective tool for enhancing consumer engagement and trust in agricultural sectors.